Crop-livestock integration focus of Agricultural value chain exhibition in Ethiopia - Hernández, S.V. (International Livestock Research Institute, 2011)
On March 31, 2011, IPMS and the Oromia Bureau of Agriculture organized an exhibition on Agricultural Value Chains in Bishoftu/Debrezeit. Here, Silvino Vergas Hernàndez explains the importance of the exhibition to share progress made in agriculture and crop-livestock integration.